Diets for in vivo inoculation of Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) (Lefavirales: Baculoviridae) - Lorena Contarini Machado; Hugo José Gonçalves dos Santos Junior; Laura Vaillant Ribeiro Mauri; Julianne Almeida Rodrigues; Nathália Puppim de Oliveira Benachio; Hugo Bolsoni Zago; Stella Arndt (Acta Scientiarum. Biological Sciences, 2025)
The Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) has been studied and applied in controlling the fall armyworm, Spodoptera frugiperda. This pest serves as the primary host for in vivo replication of this biological control agent. For viral inoculation, the virus is introduced into an artificial diet, which is also used for large-scale host multiplication. In this study, we tested more cost-effective diets to optimize the viral inoculation stage. Each diet was treated with the virus and monitored daily for host mortality. Viral production parameters were subsequently quantified. Although the evaluated diets did not achieve the same yield levels as those used for large-scale S. frugiperda multiplication, the D7 diet showed similar cost-effectiveness to the D2 diet in terms of producing one dose per hectare. Additionally, larvae consuming diets higher in crude protein exhibited reduced viral polyhedra production.